2018
DOI: 10.1021/acsaem.8b00838
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Based Natural Deep Eutectic Mixtures as Green Intercalating Solvents for High-Yield Preparation of Stable MoS2 Nanosheets: Application to Electrocatalysis of Hydrogen Evolution Reaction

Abstract: Wide applicability of nanosized MoS 2 in diverse research fields including optoelectronics, biomedicine, energy storage, and conversion is a motivation for investing efforts in green, low-cost, and efficient synthesis of these nanomaterials. To date, various methods for the synthesis of MoS 2 nanosheets have been reported, most of which use toxic organic solvents in appreciable amounts. In the present report, we introduced a mechanical exfoliation approach in which bulk MoS 2 is converted to two-dimensional na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 71 publications
(101 reference statements)
2
27
0
Order By: Relevance
“…[102][103][104][105] Besides, DESs have attracted interest in exfoliating layered nanomaterials. [106] It should be noted that the study of using DES to prepare new materials is still in its infancy, especially for those related to energy storage applications. In this section, we focus on discussing the synthesis of functional materials with DESs for energy storage applications.…”
Section: Energy Storage Materials Synthesized Using Dessmentioning
confidence: 99%
See 1 more Smart Citation
“…[102][103][104][105] Besides, DESs have attracted interest in exfoliating layered nanomaterials. [106] It should be noted that the study of using DES to prepare new materials is still in its infancy, especially for those related to energy storage applications. In this section, we focus on discussing the synthesis of functional materials with DESs for energy storage applications.…”
Section: Energy Storage Materials Synthesized Using Dessmentioning
confidence: 99%
“…Mohammadpour et al developed DESs based on natural sugar as green intercalating solvents for the preparation of stable dispersion of MoS 2 nanosheets. [106] Recently, they found that water can modulate the molecular arrangement of this DES and can effectively regulate the efficiency of preparing both MoS 2 and graphene nanosheets. [126] Besides, Sang and co-workers applied a DES composed of ChCl and EG with a molar ratio of 1:2 to exfoliate a layered metal-organic framework (i.e., MAMS-1).…”
Section: Dess As Exfoliation Agents For Nanomaterialsmentioning
confidence: 99%
“…Choline chloride was dried under vacuum over silica gel in a desiccator prior to use. The NADESs prepared and used in this study are as follows: glucose-fructose-sucrose-water (1:1:1:11) (GFSW), glucose-fructose-water (1:1:11) (GFW), glucose-sucrose-water (1:1:11) (GSW), fructose-sucrose-water (1:1:11) (FSW) [54], choline chloride (ChCl)-glucose-water (5:2:5) (CGW), ChCl-fructose-water (5:2:5) (CFW), ChCl-sucrose-water (4:1:4) (CSW) [55], ChCl-lactic acid (1:2) (CLa) [44], ChCl-malonic acid (1:1) (CMa) [55], ChCl-ethylene glycol (1:2) (CEG) [38] and ChCl-glycerol (1:2) (CGly) [56].…”
Section: Preparation Of Nadessmentioning
confidence: 99%
“…14 To tackle the compatibility and stability factors, several additional studies were conducted to prepare functionalized MoS 2 nanosheets. 79,[81][82][83] Accordingly, high efficiency polyphenol assisted liquid exfoliation was used as a green method to produce layered MoS 2 nanosheets with tannic acid (TA-MoS 2 ). 83 Due to their improved stability and compatibility, TA-MoS 2 nanosheets were successfully incorporated into the polyamide layer, forming a TFN NF membrane with superior performance.…”
Section: Mos 2 Incorporated Tfn Membranesmentioning
confidence: 99%